2010
DOI: 10.4319/lo.2010.55.3.1248
|View full text |Cite
|
Sign up to set email alerts
|

Can photoinhibition control phytoplankton abundance in deeply mixed water columns of the Southern Ocean?

Abstract: To study how natural Southern Ocean phytoplankton communities acclimate to rapid fluctuations in irradiance levels that result from deep wind-driven mixing of the upper water column, we measured their fluorescence properties (Fv : Fm, maximum quantum yield of photosystem II; and qN, non-photochemical quenching) and pigment composition. Values of Fv : Fm were low (, 0.46) and qN was high (. 0.67) throughout the upper mixed layer (UML). Short-term (20-min) exposure to incident surface irradiance strongly reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 60 publications
1
64
0
1
Order By: Relevance
“…The generally higher contribution of diatoms in the CHEMTAX data might be due to the rather unspecific marker pigment fucoxanthin in diatoms and the overrepresentation of dinoflagellates in the 454 data (gene copy number issue). The higher importance of diatoms is in agreement with the findings of Landry et al (2001) and Alderkamp et al (2010), who described an enhanced importance of larger cells and a greater contribution of diatoms south of the PF. Ning et al (1996) also observed a dominance of diatoms in cold Antarctic waters and dinoflagellates dominating in the warmer waters north of the SAF.…”
Section: Community Compositionsupporting
confidence: 91%
“…The generally higher contribution of diatoms in the CHEMTAX data might be due to the rather unspecific marker pigment fucoxanthin in diatoms and the overrepresentation of dinoflagellates in the 454 data (gene copy number issue). The higher importance of diatoms is in agreement with the findings of Landry et al (2001) and Alderkamp et al (2010), who described an enhanced importance of larger cells and a greater contribution of diatoms south of the PF. Ning et al (1996) also observed a dominance of diatoms in cold Antarctic waters and dinoflagellates dominating in the warmer waters north of the SAF.…”
Section: Community Compositionsupporting
confidence: 91%
“…Indeed, on the basis of the maximum quantum yield of PSII (Fv : Fm), Doblin et al (2011) suggested that phytoplankton in the western Australian SAZ (experiments 1 and 2) were iron limited, whereas those in the Australian PFZ and eastern SAZ (experiments 3 to 7) were iron sufficient. Over the Greenwich meridian Fv : Fm was consistently below suboptimal levels (Alderkamp et al 2010), potentially indicating iron limitation in experiments A to I, and although Fv : Fm was not assessed in the Drake Passage transect, the maximal iron concentrations ($ 1 nmol L 21 ; M. Klunder pers. comm.)…”
Section: Discussionmentioning
confidence: 95%
“…Weddell Sea Deep Water (WSDW) is separated from WDW by a temperature drop (20.7 , h , 0uC) and collected from depths , 3500 m. The deepest water mass north of the Southern Boundary of the ACC is Antarctic Bottom Water The phytoplankton community in the Subtropical and Subantarctic Zones is dominated by nanoflagellates with significant numbers of dinoflagellates, particularly at A4 and B1 (Bown et al 2011;Boye et al 2012). The rest of the study area is diatom dominated, apart from B7 (62uS) where Phaeocystis antarctica is most abundant (Alderkamp et al 2010). In this area, between 61-64uS, a bloom of P. antarctica was observed during the previous cruise (ANT24-2, December 2007-January 2008) after the spring sea ice retreat and was also visible by chlorophyll a estimations from remote sensing .…”
Section: Resultsmentioning
confidence: 99%